2023
DOI: 10.3390/ijms241814331
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Glycans in the Mucus Layer of Shark and Skate Skin

Etty Bachar-Wikstrom,
Kristina A. Thomsson,
Carina Sihlbom
et al.

Abstract: The mucus layer covering the skin of fish has several roles, including protection against pathogens and mechanical damage. While the mucus layers of various bony fish species have been investigated, the composition and glycan profiles of shark skin mucus remain relatively unexplored. In this pilot study, we aimed to explore the structure and composition of shark skin mucus through histological analysis and glycan profiling. Histological examination of skin samples from Atlantic spiny dogfish (Squalus acanthias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…These proteins could, in principle, be from either cellular sloughing, a central process in skin physiology, or actively secreted to the mucus. The fact that more proteins were identified in spiny dogfish than catsharks is consistent with a previous study of ours in which less glycans were found in chain catshark skin and may be attributed to the tissue absorption sampling method, which was developed for teleost fish, or represent true biological differences such as a thinner mucus protein layer in chain catsharks [26]. Due to the importance of the mucus as a defense barrier, we focused our attention on the proteins that may have immune system roles.…”
Section: Protein Categorizationsupporting
confidence: 91%
See 2 more Smart Citations
“…These proteins could, in principle, be from either cellular sloughing, a central process in skin physiology, or actively secreted to the mucus. The fact that more proteins were identified in spiny dogfish than catsharks is consistent with a previous study of ours in which less glycans were found in chain catshark skin and may be attributed to the tissue absorption sampling method, which was developed for teleost fish, or represent true biological differences such as a thinner mucus protein layer in chain catsharks [26]. Due to the importance of the mucus as a defense barrier, we focused our attention on the proteins that may have immune system roles.…”
Section: Protein Categorizationsupporting
confidence: 91%
“…We found mucin-5B and 5B-like (catshark, dogfish, respectively), mucin-2-like (dogfish), as well as von Willebrand factor domain (vWFD)-containing protein (dogfish, catshark), which all are large, secreted gel-forming mucins harboring a cysteine-rich domain that strengthens the mucus barrier [60]; however, the vWFD can also be found in other, non-glycosylated, proteins. Thus, despite the sharks not appearing "slimy" as bony fish, they are indeed covered by mucins albeit with a thinner layer [26]. A study from 2013 on gilthead sea bream (Sparus aurata) skin showed that mucin-2 and mucin-2-like are expressed at relatively low levels and that probiotics [61] and bacterial infection [62] increased mucin-5B expression.…”
Section: A0a4w3jxk3mentioning
confidence: 99%
See 1 more Smart Citation